Marketing’s Interfunctional Interfaces - MONTGOMERY, David B. (Institutional Knowledge at Singapore Management University, 1997)
This paper first introduces the purposes and processes of the Marketing Science Institute's Workshop on Interfunctional Interfaces: The Management of Corporate Fault Zones. The motivating issues of value migration and market orientation are considered next followed by discussion of marketing's paradigm shift. The last half of the paper deals with several management problems and research issues which were identified during the workshop.Hopefully, these questions and research needs will help to accelerate development of research into these interface issues.